Redescription of Apobaetis lakota McCafferty, 2000 (Ephemeroptera: Baetidae) and description of two new species from Brazil - Cruz, Paulo Vilela; Boldrini, Rafael; Hamada, Neusa (Zootaxa, 2020)
The genus Apobaetis Day is known by its small size and larval shifting-sand habitat preference (psammophilous). Three species of this genus are recorded in North America, from these, only Apobaetis lakota McCafferty needs to be redescribed because its original description is incomplete, turning difficult to distinguish it from species with similar morphology. Therefore, one of the objectives of this study is to redescribe A. lakota. Based on this redescription, two new species from Brazil, with similar morphology could be identified and are described (Apobaetis biancae sp. nov. and Apobaetis jacobusi sp. nov.). Apobaetis lakota can be differentiated by the labrum rectangular, distal margin without medial emargination, medial area of distal margin with three sockets of setae on dorsal surface; maxillary palp long, more than 2.0× the length of galea-lacinia, segment I with the same length as galea-lacinia; lingua subcircular with one medial lobe; glossa distally rounded; inner projection of labial palp segment II rounded and distally directed, segment III triangular; tarsal claws 1.3× the length of tarsus, without row of denticles. Apobaetis jacobusi sp. nov. can be differentiated from other species by fore tarsal claw I with the same length of tarsus, labrum medially with two protuberances and glossa with pointed apex. Apobaetis biancae sp. nov. can be differentiated by the absence of a ventral row of long thin setae near distolateral margin of labrum, four marginal spines on the paraproct, a subrectangular hypopharynx, and by the absence of robust setae on inner margin of the glossa.